2021
DOI: 10.1101/2021.08.15.456414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the interpretation of transcriptome-wide association studies

Abstract: Transcriptome-wide association studies (TWAS), which aim to detect relationships between gene expression and a phenotype, are commonly used for secondary analysis of genome-wide association study (GWAS) results. Results of TWAS analyses are often interpreted as indicating a genetically mediated relationship between gene expression and the phenotype, but because the traditional TWAS framework does not model the uncertainty in the expression quantitative trait loci (eQTL) effect estimates, this interpretation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…To dissect whether regulation of gene expression might underlie local r g s between disease traits, we performed local r g analyses using expression quantitative trait loci (eQTLs) from eQTLGen 43 and PsychENCODE 44 , which represent large human blood and brain expression datasets, respectively ( Table 1 ). We used LAVA to study relationships between gene expression and disease traits on account of its ability to model the uncertainty in eQTL effect estimates (unlike the commonly used TWAS framework, which has been shown to have an increased type 1 error rate 45 , as a result of it not accounting for the uncertainty in the estimated genetic component of gene expression). In addition, where three-way relationships were observed between 2 disease traits and an eQTL, we computed partial correlations to determine whether correlations between disease traits could be explained by the eQTL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To dissect whether regulation of gene expression might underlie local r g s between disease traits, we performed local r g analyses using expression quantitative trait loci (eQTLs) from eQTLGen 43 and PsychENCODE 44 , which represent large human blood and brain expression datasets, respectively ( Table 1 ). We used LAVA to study relationships between gene expression and disease traits on account of its ability to model the uncertainty in eQTL effect estimates (unlike the commonly used TWAS framework, which has been shown to have an increased type 1 error rate 45 , as a result of it not accounting for the uncertainty in the estimated genetic component of gene expression). In addition, where three-way relationships were observed between 2 disease traits and an eQTL, we computed partial correlations to determine whether correlations between disease traits could be explained by the eQTL.…”
Section: Resultsmentioning
confidence: 99%
“…We restricted analyses to the 5 LD blocks highlighted in Figure 2 45,893,307), which contained genes of interest to at least one of the disease traits implicated by local ‫ݎ‬ analyses. From these LD blocks of interest, we defined genic regions (gene start and end coordinates ± 100 kb) for all overlapping protein-coding, antisense or lincRNA genes (n = 92).…”
Section: Incorporation Of Gene Expression Traits To Facilitate Functi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that naïve application of MR without sensitivity analyses may yield over 30% unreliable results 5 . A recent study further suggested that 51% of results from transcriptomewide association studies could not be confirmed by genetic colocalization 49 . Another study showed the importance of distinguishing disease-causing gene expression from diseaseinduced gene expression by evaluating reverse causality using genetic data 28,50 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used all tissue types in GTEx, regardless of disease relevance. In addition, the methodological limitations of TWAS 9,59 might affect drug discovery using GReX.…”
Section: Discussionmentioning
confidence: 99%